Effect of Occupational Health on Employee Performance - Chevy Herli Sumerli A; Poppy Hidayat; Wiwi Rumaolat; Muhammad Asir; Richard Andreas Palilingan (Budapest International Research and Critics University, 2022)
Human resources are one of the important components in the role of advancing and developing a company. Without human resources with good quality, the company will find it difficult to run optimally. Therefore, human resources must be managed properly in order to produce a quality performance in achieving company goals. The purpose of this study is to analyze effect of occupational health on employee performance. This research uses explanatory research. The population of this study are all employees of CV Total Listrik Perkasa which consisted of 50 employees. From a population consisting of 50 employees contained in CV Total Listrik Perkasa, this study took all samples from that population. This study uses data analysis of partial test (t). The results show that occupational health has a positive and insignificant effect on employee performance.